Sistem Pakar Diagnosa Penyakit pada Tanaman Padi Kecamatan Satarmese Kabupaten Manggarai Provinsi Nusa Tenggara Timur Berbasis Web dengan Metode Forward Chaining - Jeraman, Firgilius; Faizah, NM; Koryanto, Lucky (Computer Journal, 2023)
Rice diseases are adverse conditions in rice caused by environmental factors, humans, and microorganisms such as viruses, bacteria, and fungi. Farmers do not understand how to determine the nature of disease and how to deal with diseases that affect rice. Farmers suffer a lot of losses due to late diagnosis, and have trouble meeting advice because they move around rather than stay in specific advice places, confusing yields. A frequently used method in expert systems is the forward chain method. This approach was chosen because it is an evolution process that begins by selecting a collection of data or facts and draws conclusions based on the selected facts. Based on the results of the system design, users of the program can diagnose rice diseases by inputting data and facts as symptoms occurring in rice, and obtain results that enable them to determine the type of disease and preventive measures increase a disease affecting rice.